A case of direct inguinal hernia incarceration after transperitoneal robot‐assisted radical prostatectomy. Issue 3 (1st February 2022) - Nakamura, Kenichi; Shibasaki, Susumu; Fukaya, Kosuke; Nakauchi, Masaya; Tanaka, Tsuyoshi; Inaba, Kazuki; Shiroki, Ryoichi; Uyama, Ichiro; Suda, Koichi
Abstract: In this study, we report a case of incarcerated direct inguinal hernia (DIH) after robot‐assisted radical prostatectomy (RARP) in a patient with concomitant DIH. The 71‐year‐old man underwent RARP. Six days later, he developed a right DIH incarceration. His laparoscopy findings revealed an incarcerated intestine that was adherent to the hernia orifice. After reducing the hernia, the peritoneum was found to be defective in the right DIH orifice. The DIH was then repaired via the Lichtenstein method. The patient was discharged without complications on postoperative day 13. No recurrence was observed at 3‐year follow‐up. When repair and peritoneum closure for concomitant DIH are not performed in RARP, it should be kept in mind that the nonrepaired concomitant DIH orifice may develop intestinal incarceration and adhesion to the hernia orifice without the peritoneum immediately after RARP.